(untitled) (Research, Society and Development, 2020)
Food safety is a global concern. Several surveys have consistently found contaminated or inadequate food being marketed in retail. In Brazil, several regions have been the target of outbreaks or incidents involving contaminated food, evidencing itself as a public health problem. Despite the existence of food control and control bodies, several fragilities in inspection prevent the food from reaching the final consumer. Among the foods constantly investigated, we highlight the beef, main source of protein, vitamins and minerals of the Brazilian population. In this way, the research had as objective to evaluate the microbiological and physical-chemical parameters of six butchers located in three districts of the south zone of the city of Macapá-AP. Samples were collected in two butchers from each neighborhood of the city of Macapá-AP, and were submitted to tests for microbiological identification (thermotolerant coliforms, Salmonella spp and Staphylococcus coagulase positive) and physicochemical (pH and temperature of exposure). It was observed that 100% of the samples collected in the butchers of the three districts of the south zone Macapá-AP were positive for thermotolerant coliforms and 94.44% for Staphylococcus coagulase positive and the values of NMP / g for thermotolerant coliforms presented high values, physicochemicals were identified that the pH of most of the establishments were outside the standards of Norm No. 83, however, the packaging temperature was in accordance with the regulations. Therefore, the research revealed that the establishments that market the ground beef presented hygienic-sanitary problems, which causes concern regarding the health of the population of the studied districts.